The role of the state in foreign borrowing by developing countries - Susanne Schattner; Klaus Stanzel (Intereconomics, 1985)
The debt crisis that has been rumbling for many years repeatedly necessitates fresh rescheduling negotiations. These debt rescheduling conferences bring together two fundamentally different partles: on the one side are the emissaries from the big international banks and on the other the government representatives from the debtor country in question.
Keywords: 330; Indebtedness